COLIFORM AND NON COLIFORM BACTERIA THAT ISOLATED FROM RESPIRATORY TRACT OF BALI CATTLE - Wiliantari, Putri; Besung, I Nengah Kerta; Tono PG, Ketut (Buletin Veteriner Udayana, 2018)
The main purpose of this study is to determine the coliform and non coliform bacteria at the respiratory tract of Bali cattle that raised at the lowlands and highlands. 36 Samples were taken on calves, heifers, and adults, then grown on Salmonella Shigella Agar medium by spreading method. Coliform colonies and non coliform colonies were analyzed variably and followed by Least Significant Difference (LSD) test. The results showed that the number of coliform bacteria of bali cattle at the highlands was 1287.96 CFU/g and at the lowlands was 643.9798 CFU/g and non coliform bacteria at the highlands was 162.2464 CFU/g and at the lowlands as much as 81.12321 CFU/ g. Coliform and non coliform bacteria were obtained at the highlands and the lowlands showed no significant differences.